2019
DOI: 10.1016/j.ijscr.2019.10.046
|View full text |Cite
|
Sign up to set email alerts
|

The use of free fibula-flexor hallucis longus osteomuscular flap for calcaneal reconstruction after partial calcanectomy for the chronic osteomyelitis: A case report

Abstract: HighlightsCalcaneal osteomyelitis is difficult to eradicate.Calcaneal debridement and infection control are critical.Osteomuscular flaps offer a stable and effective reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…In cases of OC, the primary surgical goal is the complete removal of necrotic tissues; however, more radical interventions are sometimes necessary. 5 , 7 , 26 , 29 , 41 , 42 …”
Section: Discussionmentioning
confidence: 99%
“…In cases of OC, the primary surgical goal is the complete removal of necrotic tissues; however, more radical interventions are sometimes necessary. 5 , 7 , 26 , 29 , 41 , 42 …”
Section: Discussionmentioning
confidence: 99%
“…When looking at the use of femoral head allografts to augment acetabular bone loss post-THA, Butscheidt et al 20 found that the allograft showed intact structure, significantly higher mineralization than the host bone, and an average of 7.2 mm of ingrowth with a mean follow-up of 12.9 years. Subtalar, 19 calcaneocuboid, 19 , 21 and fusions to the remaining calcaneus 7 , 8 have been used to help manage large defects of the calcaneus. We decided upon a subtalar fusion through the allograft and remaining calcaneus as it would preserve ankle joint range of motion and inversion/eversion ability while providing strong hindfoot structural support.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors argued for harvesting muscle to fill the dead space in the floor of the mouth, 18 and antrum, after partial calcanectomy. 6 …”
Section: Discussionmentioning
confidence: 99%
“… 2 The fibula osteo-cutaneous flap is used for reconstruction of many anatomical defects. They are used in reconstruction of mandible, maxilla, 3 clavicle, 4 long bones (humerus, radius, ulna, femur, tibia), 5 vertebrae, calcaneum, 6 etc. The length of the bone that can be harvested, presence of muscle, and large skin paddle that can be harvested have added to the advantages of using fibula flap for reconstruction purposes.…”
Section: Introductionmentioning
confidence: 99%